Well-being in using TikTok amongst young people in China - Lian, Tang; Omar, Siti Zobidah; Bolong, Jusang; Mohd Zawawi, Julia Wirza (Human Resource Management Academic Research Society, 2022)
TikTok is a prevalent social media video application used in contemporary society, which has appealed great interest from the young people. This study examined the level of overall well-being in using TikTok amongst young people in China as guided by the PERMA theory of well-being. This study adopted a quantitative approach via questionnaire survey to collect data. A sample of 405 young people participated in the survey. Data analysis was performed based on both descriptive and inferential analysis. The results showed that the majority of young people reported a high level of comprehensive well-being in using TikTok. Specifically, the domains, which included positive emotion that contributed the highest towards the overall well-being, while the meaning domain contributed the lowest. Additionally, the findings revealed that young people with a Doctor of Philosophy (PhD) presented a lower level of well-being compared to other groups of education level. This study suggested that the operators of TikTok platform should perfect the functions and strengthen by vetting the quality of video contents on TikTok to increase the level of users’ well-being. The results are also beneficial to the Chinese government, which could provide references to the government to implement strategies on youth development through the TikTok platform.